Application of a variational method to flow over a flat plate in the entrance region with variable physical properties. - Su, Yi-Lung. (University of Ottawa (Canada), 1970)
A variational method has been used to solve the flow over a flat to in the entrance region at constant wall temperature. The physical properties, i.e. thermal conductivity and viscosity, were assumed to be linear functions of temperature in the study. Two coupled equations were derived from the variational formulation and then solved by the analog/hybrid computer. Consequently, momentum boundary layer thickness, thermal boundary layer thickness, local Nusselt number and local friction factor were found for the flow. A comparison of the constant properties case was made between the results from this study and those obtained the exact solution.
Keywords: Engineering, Mechanical.